PEMANFAATAN LIMBAH SERBUK KAYU KARET (Hevea brasiliensis) DAN SERBUK PELEPAH KELAPA SAWIT (Elaeis guineensis) SEBAGAI BAHAN BAKU BIOPELET - Muhammad Syamsudin; Muhammad Faisal Mahdie; Noor Mirad Sari (Jurnal Sylva Scienteae, 2022)
Rubber wood waste from sawmills is in the form of powder which is still rarely used and usually for burning, in the sawmill industry the total waste is 50.8% of the raw material processed. Post-pruning oil palm fronds waste is also not widely used, where each hectare of oil palm plantations can produce as much as 486 tons of dry fronds and 17.1 tons of dry palm leaves / year. Based on these wastes, it can be used as raw material for biopelets. The quality of the biopellets produced from rubber wood sawdust combined with palm frond powder based on American standards (PFI), has obtained the recommended formulation, namely the ratio of 75% rubber wood powder powder and 25% rubber wood frond powder (Treatment B). With a density of 0.4909 g / cm3, a moisture content of 5.5625%, 77.7000% of flying substances, 11.6924% of bound carbon, 1.8100% of ash, and a calorific value of 4.067.63 cal / gLimbah kayu karet dari penggergajian berupa serbuk yang masih jarang dimanfaatkan dan biasanya untuk di bakar, pada industri penggergajian total limbah sebesar 50,8% dari bahan baku yang diolah. Limbah pelepah kelapa sawit pasca pruning juga belum banyak dimanfaatkan, yang setiap hektarnya kebun sawit dapat menghasilkan sebanyak 486 ton pelepah kering dan 17,1 ton daun sawit kering/tahun. Berdasarkan dari limbah-limbah tersebut sehingga dapat dimanfaatkan menjadi bahan baku biopelet. Kualitas biopelet yang dihasilkan dari serbuk kayu karet yang dipadukan serbuk pelepah kelapa sawit berdasarkan standar Amerika (PFI), telah diperoleh formulasi yang direkomendasikan yaitu pada perbandingan serbuk 75% serbuk kayu karet dan 25% serbuk pelepah kayu karet (Perlakuan B). Dengan kerapatan 0,4909 g/cm3, kadar air 5,5625 %, kadar zat terbang 77,7000%, karbon terikat 11,6924% kadar abu 1,8100%, dan nilai kalor 4.067,63 kal/g